THE IMPORTANCE OF PLANTS IN HUMAN LIFE AND THEIR DIVERSITY - Fayziyeva Gulhayo Erkin qizi (Journals Park Publishing, 2024)
Plants are an essential component of life on Earth, contributing to ecological balance, human health, and the global economy. This article explores the critical roles plants play in human life, including their contributions to food security, medicine, industry, and the environment. Additionally, the article examines the vast diversity of plant species, highlighting their ecological, economic, and cultural significance. Through a review of existing literature, this study emphasizes the need for sustainable management and conservation of plant biodiversity to ensure their continued benefits for current and future generations.
Keywords: Plants, biodiversity, human life, food security, medicine, ecological balance, conservation, sustainable management.